2014
DOI: 10.1016/j.bjid.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Dried blood spot testing for the antenatal screening of HTLV, HIV, syphilis, toxoplasmosis and hepatitis B and C: prevalence, accuracy and operational aspects

Abstract: The use of dried blood spot may represent a secure way to expedite access to results of vertically transmitted diseases in the prenatal period, particularly in regions with scarce healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Such advantages have been demonstrated by the experience and results of neonatal screening programs over the last 40 years for a large group of pathologies. 6 In the present study, it was verified that the frequencies of the infections, detected on paper filter, in pregnant women in the two studied regions in general were compatible with those found in other regions of the country, except for syphilis and the presence of sickle cell trait which presented a higher percentage. In addition, due to the implementation phase of the Programa da Rede Cegonha (Stork Network Program) and considering the fact that the data represents its initial phase, demanding expansion and consolidation in order to achieve better results, coverage rates in the South and Southwest macro-regions in Bahia were considered satisfactory.…”
Section: Variablessupporting
confidence: 86%
See 1 more Smart Citation
“…Such advantages have been demonstrated by the experience and results of neonatal screening programs over the last 40 years for a large group of pathologies. 6 In the present study, it was verified that the frequencies of the infections, detected on paper filter, in pregnant women in the two studied regions in general were compatible with those found in other regions of the country, except for syphilis and the presence of sickle cell trait which presented a higher percentage. In addition, due to the implementation phase of the Programa da Rede Cegonha (Stork Network Program) and considering the fact that the data represents its initial phase, demanding expansion and consolidation in order to achieve better results, coverage rates in the South and Southwest macro-regions in Bahia were considered satisfactory.…”
Section: Variablessupporting
confidence: 86%
“…The use of paper filter for screening on pregnant women has shown to be quite effective, both in economic, as biosecurity and reliability aspects. 6 In this study, it was sought to estimate the rate of early detection of pathology screening, through the use of paper filter, as well as the coverage on adhesion and scope on the Programa de Triagem Pré-natal em Papel de Filtro da Rede Cegonha (Prenatal Screening Program on Paper Filter from the Stork Network), in the South and Southwest macro-regions in the State of Bahia. In addition, there was a concern to trace these pregnant women's epidemiological profile on the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…A large prospective study of pregnant women in Europe, also used DBS samples from France, England and Germany [ 35 ], and it is worthwhile to note that of the 104 samples repeatedly reactive by particle agglutination test or ELISA, only 83 could be confirmed by Western blot or Line Immuno-Assay. Furthermore, a recent study comparing 692 DBS and their corresponding venous blood samples for the serological detection of several infections, found that both methods successfully detected several cases, including one HTLV infection [ 29 ], although no confirmation assay was used. Finally, one large study analyzed 55,293 DBS for HTLV seroprevalence, and although Western blot was not used for confirmation, it was possible to investigate the corresponding blood samples for confirmation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…DBS were shown to be reliable for detecting anti-HIV-1/HIV-2 antibodies and serological markers of other pathogens, using either in-house or commercial assays to analyze the eluates [ 27 , 28 ]. The use of DBS in the detection of anti-HTLV antibodies has also been validated in several studies [ 29 31 ]. One early study initially established the methodology using simulated DBS, (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of syphilis, EIA is used to detect treponemal antibodies of both classes (IgG and IgM). These tests have good sensitivity and specificity and have been used in some settings in Brazil as routine antenatal screening, including the investigation of other infections in the same blood sample [ 40 - 43 ].…”
Section: Reviewmentioning
confidence: 99%